The Content of Some Metal Pollutants in Efeluents of Leather Tanning Industry - Sanhouri, Naima Y.; Abd Elaziz, Mohamed (Gezira Journal of Engineering and Applied Sciences, 2018)
This research work was conducted to determine the metal pollutants namely chromium, iron, manganese and zinc that result from the process of leather tanning industry in Khartoum. The determinations were performed in samples collected from wastewaters and tap water of Khartoum Tannery and from two locations at Soba Treatment Plant; (Soba In the inlet and Soba Out the outlet). The results were compared to the permissible levels stated by FAO and Sudanese Standard and Metrology Organization (S.S.M.O). Analysis of Tannery wastewaters showed that: the mean concentrations of chromium, iron, manganese are higher than S.S.M.O and FAO permissible level. The mean concentrations of zinc are below the permitted level stated by S.S.M.O but slightly higher than that of FAO. Analysis of Soba In wastewaters showed that the mean concentrations of chromium, iron and manganese were higher than S.S.M.O and FAO permissible level. Analysis of Soba Out wastewaters showed that: mean concentrations of iron, and chromium are higher than S.S.M.O. and manganese mean concentration is higher than S.S.M.O and FAO permissible level. Reduction of tannery waste pollution impacts can be achieved by applying different treatment techniques to protect the environment and human health.